Traumatic Bilateral Diaphragmatic Ruptures in a 6-Year-Old Boy - Sung Jin Kim; Hyuck Kim; Jun Ho Lee (Journal of Trauma and Injury)
Traumatic diaphragmatic rupture is an unusual finding that may occur after blunt trauma. In addition, diaphragmatic rupture occurring bilaterally is extremely rare. We experienced a 6-year-old boy with bilateral diaphragmatic rupture, whom survived after surgical treatment by open thoracotomy but, complicated with spinal cord injury discovered after surgery.